Targeting Obesity and Diabetes to Treat Heart Failure with Preserved Ejection Fraction - Altara, Raffaele; Giordano, Mauro; Nordén, Einar S.; Cataliotti, Alessandro; Kurdi, Mazen; Bajestani, Saeed N.; Booz, George W. (Frontiers in Endocrinology, 2017)
Heart failure with preserved ejection fraction (HFpEF) is a major unmet medical need that is characterized by the presence of multiple cardiovascular and non-cardiovascular comorbidities. Foremost among these comorbidities are obesity and diabetes, which are not only risk factors for the development of HFpEF, but worsen symptoms and outcome. Coronary microvascular inflammation with endothelial dysfunction is a common denominator among HFpEF, obesity, and diabetes that likely explains at least in part the etiology of HFpEF and its synergistic relationship with obesity and diabetes. Thus, pharmacological strategies to supplement nitric oxide and subsequent cyclic guanosine monophosphate (cGMP) – protein kinase G (PKG) signaling may have therapeutic promise. Other potential approaches include exercise and lifestyle modifications, as well as targeting endothelial cell mineralocorticoid receptors, non-coding RNAs, sodium glucose transporter 2 inhibitors, and enhancers of natriuretic peptide protective NO-independent cGMP-initiated and alternative signaling, such as LCZ696 and PDE9 inhibitors. Additionally, understanding the role of adipokines in HFpEF may lead to new treatments. Identifying novel drug targets based on the shared underlying microvascular disease process may improve the quality of life and lifespan of those afflicted with both HFpEF and obesity or diabetes, or even prevent its occurrence.